(untitled) (Global Journal of Computer Science and Technology, 2017)
Video compression is the one which has highest demand in the area of video processing Motion estimation ME is the basic of Video compression There are several algorithms to estimate the motion estimation of current block in reference frame In the view of this a new novel technique has been proposed in namely Logarithmic Search with Three Step Reduction LSTSR which is computationally more efficient than many of the existing techniques Simulation result shows that it performs better than that of Three Steps Search TSS New Three Step Search NTSS and reduces the checking points by almost 50 than that of TSS